Manajemen Stres dan Kedisiplinan sebagai Upaya Peningkatan Efektivitas Pegawai di Dinas Komunikasi dan Informatika Kabupaten Ciamis - Ading Rahman Sukmara (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to analyze the effect of work stress and work discipline on the effectiveness of human resources (HR) in employees of the Communication and Information Service (Diskominfo) of Ciamis Regency. The effectiveness of human resources is crucial for the success of government agencies in public services and information technology management, where the optimal performance of employees is influenced by stress management and discipline levels. This study adopted a quantitative-descriptive method by distributing questionnaires to 40 respondents who were selected through random sampling techniques. The data testing included validity, reliability, and multiple linear regression analysis tests to test the relationship of independent variables (work stress X_1 and work discipline X_2) to bound variables (HR effectiveness Y). The results of the analysis show that work stress and work discipline simultaneously have a significant effect on the effectiveness of human resources. Partially, work stress has a negative influence, indicating that increased work stress tends to reduce the effectiveness of human resources. On the contrary, work discipline has been shown to have a positive effect, showing that the higher the employee's discipline, the more their work effectiveness will increase. Therefore, the conclusion emphasizes that increasing the effectiveness of human resources requires the implementation of effective work stress management and the establishment of a consistent work discipline culture. This effort is important to create a conducive work environment, increase productivity, and strengthen the performance of the state civil apparatus in supporting an electronic-based government system and digital public services.